Oral Clefting in China Over the Last Decade: 205,679 Patients - Kling, Rochelle R. (Plast Reconstr Surg Glob Open, 2014)
BACKGROUND: China is the most populated country and has one of the highest prevalences of oral clefting. The present study reports the epidemiology and surgical procedures performed on the largest reported cohort of individuals with clefting in China. METHODS: A retrospective review of patients who received cleft repair through Smile Train in China from 2000 to 2011 was conducted. Data on demographics, cleft characteristics, associated malformations, pregnancy and family history, and surgical technique were analyzed using SPSS (IBM, Chicago, Ill.). RESULTS: A total of 205,679 patients underwent 209,169 cleft procedures. Cleft lip and palate (42.7%) was most common followed by isolated cleft palate (32.4%) and isolated cleft lip (24.9%). Males accounted for 63.5% of cases. The average age at initial surgery was 6.12 years. By 2011, this decreased to 1.8 years of age for lip repair and to 5.9 years of age for palate repair. The preferred techniques were rotation-advancement (55%) for unilateral lip repair and Von-Langenbeck (38%) and pushback (39%) for palate repair. The percentages of cases with associated anomalies and surgical complications were 12.8% and 0.36%, respectively. CONCLUSIONS: This study provides insight into cleft care in China as it reports the largest cohort of cleft patients treated by surgeons to date. Our results generally follow trends previously reported in China and developed countries. The male:female ratio for cleft palate patients was higher than expected. The average age at primary repair is higher than recommended, but seems to be decreasing.